Antiulcerogenic potential of Salvia officinalis L. extract in rats - Taís Regina Fiorentin, Michela Bianchi De Mello, Aline Maria Krube Aquino, Bruna Alexsandra Rigo, Carla Giane Loss, Melissa Schwanz, Arno Ernesto Hofmann Junior, Sandra Manoela Dias Macedo (Journal of Applied Pharmaceutical Science, 2013)
The objective of this paper was to evaluate the antiulcer activity of a crude ethanol extract of Salvia officinalis L. in a gastric lesion induction model. Male Wistars rats were housed in groups of five and fasted 12 hours before the experiment, receiving only water ad libitum. The experimental groups received oral doses of 50, 75, 100 and 150 μg/kg of the extract and the negative and positive control groups received distilled water and omeprazol (30mg/kg), respectively. One hour after each respective oral dose, the ulcer was induced with absolute ethanol. a further hour after induction, the animals were euthanized by CO2 camera, the stomachs removed and opened along the greater curvature. Data was statistically analysed using analysis of variance (ANOVA) followed by the Tukey method (p
Keywords: Salvia officinalis L., antiulcero